Народный Совет и Управление Города и Гмины в Лосицах в 1973-1990 гг. – история фондообразователя и архивного фонда = Narodnyy Sovet i Upravleniye Goroda i Gminy v Lositsakh v 1973-1990 gg. – istoriya fondoobrazovatelya i arkhivnogo fonda - MAGIER, Dariusz (Historia i Świat, 2016)
Following the end of World War II, local authorities were subjected to local representative bodies, which were an affiliated entity headed by a State National Council. Since 1 January 1973, local national council was empowered to act as both a national and basic local authority on behalf of a gmina (lowest level of administrative division) or a town with a neighbouring gmina. Whereas a gmina’s or town and gmina’s governor served as a one-man administrative and executive body. The author presents the interrelated activity of national councils and local administrative bodies across Poland in 1973-1990 based on the example of the Municipal and Communal National Council as well as the Municipal and Communal Office both based in Łosice. He portrays these authorities in respect to archival research, describes their structural history as those responsible for compiling documents and characterizes archival records created by them.